Utopia Of a Classless Society In Roald Dahl's Charlie and the Chocolate Factory: Marxist Study - Azriel Akbar Faizal; Rahayu Puji Haryanti (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
This study addresses the problem of how Roald Dahl's Charlie and the Chocolate Factory reflects the dynamics of class struggle and the concept of a classless society through a Marxist perspective. The analysis employs a Marxist literary criticism framework to examine the narrative's portrayal of socioeconomic themes, focusing on the symbolic representation of the chocolate factory as a site of production and class interaction. The findings reveal that while the narrative suggests a meritocratic shift in power and advocates for moral integrity over wealth, it simultaneously exposes the underlying contradictions of a classless society. The presence of the Oompa-Loompas highlights the persistence of labor exploitation, questioning the authenticity of the proposed utopia and indicating that the narrative reinforces rather than fully resolves capitalist ideologies. The study concludes that Dahl's work, while promoting ideals of social mobility and equity, ultimately fails to achieve the Marxist vision of class eradication. Instead, it presents a diluted form of capitalism, masked as a fantasy, which invites critical reflection on the limitations of children's literature in addressing complex social issues.